Effect of different staining materials on color stability of sapphire brackets bonded with different types of light cure orthodontic adhesives (An in vitro study) - Albo Hassan, Alaa F; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2015)
Background: The demand for better esthetic during orthodontic treatment has increased nowadays, so orthodontists starting using esthetic arch wires, brackets and ligatures.Tooth colored brackets were introduced in different types of materials. Sapphire ceramic brackets are one type of esthetic brackets and their color stability remains the main concern for the clinicians and patients at the same time. The present study design to evaluate the effect of three different staining materials (pepsi, black tea and cigarette smoke) on the stainability of sapphire ceramic brackets bonded with three types of light cure orthodontic adhesives which include: Resilience, Enlight and Transbond.Materials and Methods: The sample consisted of three hundred sixty sapphire brackets. The brackets were divided according to bonding materials into three groups each group consist of one hundred twenty brackets, then each subgroup farther subdivided into four groups according to the material they were immersed (distilled water, black tea, Pepsi and cigarette smoke) with thirty brackets each, then Each group with ten brackets farther subdivided according to time interval of immersion in each media into three groups one day, seven days and fourteen days at 37Â°C in the incubator.A UV-Visible spectrophotometer (Shimadzu, UV -1800) was used to perform a light absorption test.Results: ANOVA and LSD post Hoc tests were used to identify the significant effects of the staining materials at a significance level P â‰¤ 0.05.It was found that the immersion time gradually influenced the color stability of the adhesive materials with sapphire brackets with the highest activity observed at fourteen days interval. The brackets bonded with Resilience light cure adhesive are the most type affected by staining materials, then followed by the brackets bonded with Transbond and finally the brackets bonded with Enlight light cure adhesive. For the staining materials it was found that the cigarette smoke is the most powerful staining material, followed by tea and finally pepsi. Conclusions: From the above result we can conclude that the type of adhesive must take in consideration when the esthetic brackets have been used.